2020
DOI: 10.1109/tiv.2019.2955905
|View full text |Cite
|
Sign up to set email alerts
|

Combining Planning and Deep Reinforcement Learning in Tactical Decision Making for Autonomous Driving

Abstract: Tactical decision making for autonomous driving is challenging due to the diversity of environments, the uncertainty in the sensor information, and the complex interaction with other road users. This paper introduces a general framework for tactical decision making, which combines the concepts of planning and learning, in the form of Monte Carlo tree search and deep reinforcement learning. The method is based on the AlphaGo Zero algorithm, which is extended to a domain with a continuous state space where self-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(100 citation statements)
references
References 27 publications
0
85
0
Order By: Relevance
“…and MOBIL [40] model. In the other publication from the same author [100], the action space is changed slightly by changing [65] Fig . 12.…”
Section: Driving In Trafficmentioning
confidence: 99%
“…and MOBIL [40] model. In the other publication from the same author [100], the action space is changed slightly by changing [65] Fig . 12.…”
Section: Driving In Trafficmentioning
confidence: 99%
“…We use a network architecture similar to Hoel et al [9]. Our early experiments showed that training was faster and more stable using this architecture compared to standard fully connected networks.…”
Section: Policy Networkmentioning
confidence: 99%
“…3. Illustration of the network architecture [9]. The convolutional layers allow to share the weights when processing other vehicles' states.…”
Section: Policy Networkmentioning
confidence: 99%
“…Since Deepmind's team used recent advances in training deep neural networks to develop a novel artificial agent [16]- [18], termed a deep Q-network [19], which was able to surpass the performance of all previous algorithms and achieve a level comparable to that of a professional human games tester, deep reinforcement learning (DRL) has become a useful method to solve control problems and decision-making problems [20], [21]. Unlike the above decision-making method, DRL decision-making does not need to make trial maneuvers and predict the positions at each decision-making stage.…”
Section: Introductionmentioning
confidence: 99%